Effects of Cigarette Smoking on Cardiopulmonary Fitness of Some Randomly Selected Undergraduate Students in Zaria, Kaduna State (Western Journal of Medical and Biomedical Sciences, 2023)
Cigarette smoking is a leading cause of unnecessary deaths and morbidity due to its role in lung cancer, cardiopulmonary disease (CD), ischemic heart diseases and stroke. Although, the actual mechanism of smoking in cardiopulmonary disease is not clear, smoking is well established as the primary risk factor of cardiopulmonary disease. Two hundred students of Ahmadu Bello University were involved in this study. One hundred were known smokers with a clear history of smoking while the other group (100) had no smoking history. Body mass index, body fat percentage, blood pressure, peak flow rate, skeletal muscle percentage and visceral fat were measured among the participants. The results revealed that percentage skeletal muscles and peak flow rate were significantly higher in non-smokers compared to smokers whereas systolic and diastolic blood pressure, body mass index, body fat percentage and visceral fat were significantly higher in smokers compared to the non-smokers. Evidence from this study indicates possibilities of compromise in cardiopulmonary fitness of Nigerian undergraduate smokers.
Keywords: Cardiopulmonary fitness; Cardiopulmonary disease; Cigarette smoking; Undergraduate students